Standardised criteria improve accuracy of ECG interpretation in competitive athletes: a randomised controlled trial. Issue 15 (21st March 2014) - Exeter, Daniel J; Elley, C Raina; Fulcher, Mark L; Lee, Arier C; Drezner, Jonathan A; Asif, Irfan M
Abstract : Background: Screening to prevent sudden cardiac death remains a contentious topic in sport and exercise medicine. The aim of this study was to assess whether the use of a standardised criteria tool improves the accuracy of ECG interpretation by physicians screening athletes. Methods: Design: Randomised control trial. Study population: General practitioners with an interest in sports medicine, sports physicians, sports medicine registrars and cardiologists from Australia and New Zealand were eligible to participate. Outcome measures: Accuracy, sensitivity, specificity and false-positive rates of screening ECG interpretation of athletes. Intervention: A two-page standardised ECG criteria tool was provided to intervention participants. Control participants undertook 'usual' interpretation. Results: 62 physicians, with a mean duration of practice of 16 years, were randomised to intervention and control. 10 baseline and 30 postrandomisation athlete ECGs were interpreted by the participants. Intervention participants were more likely to be correct: OR 1.72 (95% CI 1.31 to 2.27, p<0.001). Correct ECG interpretation was higher in the intervention group, 88.4% (95% CI 85.7% to 91.2%), than in the control group, 82.2% (95% CI 78.8% to 85.5%; p=0.005). Sensitivity was 95% in the intervention group and 92% in the control group (p=0.4), with specificity of 86% and 78%, respectively (p=0.006). There were 36% fewer false positives in the intervention group (p=0.006). Conclusions: ECG interpretation in athletes can be improved by using a standardised ECG criteria tool. Use of the tool results in lower false-positive rates; this may have implications for screening recommendations. Trial Registration number: ACTRN12612000641897.